The Effect of Reconstruction and Code Changes at Pedestrian Crossings to Traffic safety for Children, Grownups and Elderly: Results from a case study in Borås - Johansson, Charlotta; Leden, Lars (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
The results from studies at five different intersections in Borås are presented. At two intersections, at Hultagatan and Sjöbotorggatan, the traffic environment was reconstructed using speed reducing devices. The other three were control sites, two at Trandared School with speed reducing devices already implemented and one at Källbäcksrydsgatan with no speed reducing devices. The sites are studied before and after changes of the traffic environment (if any), before and shortly after the law was changed (1 May 2000). The new law strengthens car drivers obligation to give way to pedestrians that intend to cross the street at zebra crossings. The studies examine differences between children’s, grownups’ and elderly people’s interactions with motor traffic at zebra crossings. The frequency with which pedestrians are given way to by car drivers increased with 32 percentage points (from 17 % to 49 %) when speed cushions were implemented at Hultagatan. After the new law was enacted the giving way frequency increased to 64 %. The frequency of giving way to pedestrians increased by 9 points (from 59 % to 68 %) and 28 points (from 54 % to 82 %) at the two intersections at Trandared School when the new law was enacted. Elevating the surface at Sjöbotorggatan decreased the speed of the vehicles but had low effect on the giving way frequency because of the pedestrian’s decreased usage of the zebra crossing. No differences between giving way frequency towards children and adults were seen.